Synthesis, Antibacterial Effects, and Toxicity of Licochalcone C - Patrick Rômbola Ozanique; Alvaro Luiz Helena; Ralciane de Paula Menezes; Daniela Silva Gonçalves; Mariana Brentini Santiago; Guilherme Dilarri; Janaína de Cássia Orlandi Sardi; Henrique Ferreira; Carlos Henrique Gomes Martins; Luis Octávio Regasini (MDPI AG, 2024)
Drug-resistant bacteria constitute a big barrier against current pharmacotherapy. Efforts are urgent to discover antibacterial drugs with novel chemical and biological features. Our work aimed at the synthesis, evaluation of antibacterial effects, and toxicity of licochalcone C (LCC), a naturally occurring chalcone. The synthetic route included six steps, affording a 10% overall yield. LCC showed effects against Gram-positive bacteria (MIC = 6.2-50.0 µg/mL), Mycobacterium species (MIC = 36.2-125 µg/mL), and Helicobacter pylori (MIC = 25 µg/mL). LCC inhibited the biofilm formation of MSSA and MRSA, demonstrating MBIC50 values of 6.25 μg/mL for both strains. The investigations by fluorescence microscopy, using PI and SYTO9 as fluorophores, indicated that LCC was able to disrupt the S. aureus membrane, similarly to nisin. Systemic toxicity assays using Galleria mellonella larvae showed that LCC was not lethal at 100 µg/mL after 80 h treatment. These data suggest new uses for LCC as a compound with potential applications in antibacterial drug discovery and medical device coating.